Estymacja stałej czasowej metodą liniowej aproksymacji pochodnej funkcji ekspotencjalnej = Time constant estimation using linear approximation of the exponential function derivative - Pawłowski, Eligiusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The paper presents method for estimating the sensor`s thermal time constant using linear approximation of the exponential function derivative by the least squares method. The discussed method was used to design a new type of hot-wire anemometer. Relevant mathematical relationships, the measurement system implemented and sample measurement results obtained were also presented.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne